A repercussão geral e os recursos repetitivos em matéria tributária: a técnica do caso modelo como forma de valorização do precedente e proteção da confiança do contribuinte - Alice Gontijo Santos Teixeira (2014)
Recent changes were made to Brazilian Civil Procedure Code (Law no. 11.418/2006 and Law no. 11.672/2008) in order to introduce new form of proceedings for judging repetitive cases. The changes were inspired by a German procedural institute named Musterverfahren, created by German tort liability act for financial market (Kapitalanleger-Musterverfahrensgesetz, hereinafter as "KapMug"). According to this type of proceedings one repetitive case is selected and submitted to the Higher Court for a model trial. The ruling handed down by the Higher Court in the model trial is biding to all other repetitive cases, it is said to all cases which decisions depend on the legal question resolved in model trial using model case proceedings. Therefore, the Courts are freed of reviewing the same legal question countless times. The immediate reason for the introduction of the new form of proceedings in Brazil was the continuous increase of the workload of Higher Courts. However, besides this main purpose, the new form of proceedings is found to be an important mechanism to empower Higher Courts decisions and to promote the system integrity. It is caused by a biding effect that the ruling handed down by a Court in the model case has, which irradiates this effect to all similar cases on trial as well as to all similar cases that may be filed in the future. Therefore, the system assures that ones expectation on having the precedent applied to his or her cases are fulfilled. However, there is a serious risk in adopting this procedure as a measure of practicality, by treating different cases as if they were similar. This happens when the cases peculiarities are disregard artificially. The risk can also be aggravated by the fact that the model case proceedings have been introduced in Brazil in the appellate degree. This means that the application of the precedent is analyzed along the admission of the appeals to the higher courts. Therefore, one can wrongly neglect the need to justify the decision of applying the precedent or not. This paper analyses the procedural reform under studies of Professor Misabel Derzi, which is based on Niklas Luhmanns Systems Theory, in order to XI investigate if and to which extent the new form of proceedings cooperates on the diminution of a system complexity and on the improvement of the system capacity to protect predictability, reliability and stability. Moreover, this paper intends to examine, through Jürgen Habermas Communicative Action Theory, whether this form of proceedings is legitimate in order to allow all interested parties to participate on the elaboration of the norm that will be laid on them.Considering those theories and using tax demands as a hypothesis test because of its natural tendency to repetitiveness we conclude that although in Tax Law the law is applied massively, and although this can be efficient, the Judiciary can never abandon its mission to carry out individual justice. Moreover, as tax is an unilateral act of the State, only the Judiciary can ensure the right of the taxpayer to express their dissent (or consent) with the tax. In this sense, the procedure of the model case, now extended to the new CPC, should be understood as a tool for enhancement of the legal power of precedents, as a promotion of equality, as assurance of legal certainty and as the strengthening of the role of the superior courts in bringing uniformity to the legal system. Finally, the model case proceedings are definitely an achievement of our legal system.